Teacher Authority in Assessment-Oriented English Classroom Discourse: A Critical Discourse Analysis of In-Service Teachers in Indonesia - Feisal Aziez; Dedy Irawan; Miftahul Furqon; Aleeyah Masae; Waridatul Hikmah (IJECA (International Journal of Education and Curriculum Application), 2026)
This study examines how teacher authority is discursively constructed in English classroom interaction within assessment-oriented teacher education contexts in underdeveloped regions. While prior research has explored classroom discourse and teacher authority, limited attention has been given to how authority is constructed in assessment-based instructional videos within in-service teacher education programs, particularly in marginalized contexts. Addressing this gap, the study employs a qualitative critical discourse analytic design to analyze seven instructional videos produced by participants of the In-Service Teacher Education Program (PPG Guru Tertentu) in Indonesia. Drawing on Fairclough’s three-dimensional model, the analysis involved transcription, iterative coding of linguistic and interactional features, and interpretation across textual, discursive, and social practice dimensions. The findings show that teacher authority is constructed through directive language, structured questioning, evaluative feedback, and regulated participation, positioning students primarily as responsive participants. These patterns reflect the influence of assessment-driven teaching contexts that prioritize visible control as an indicator of competence. The study extends Critical Discourse Analysis by highlighting the performative and assessment-mediated nature of teacher authority and underscores the need for more dialogic and participatory practices in teacher education.